Revitalisasi Kolam Pancing Pujasera dalam Upaya Penguatan Sosial Ekonomi Masyarakat Desa Sumberpakem melalui Kegiatan Festival - Panuluh, M. Rapita Kun; Aziz, Ahmad Rijal; Fitriani, Devia; Athira, Dini; Purwanti, Eka Rela Pradana; Nirmalasari, Fadhilah Ayu; Romdany, Fany Eka; Fathorroji, Fathorroji; Sari, Idcha Rahma; Mashuri, Mashuri; Maulana, Mirza Much; Fadli, Fadli; Syarif, Muhammad Ilham Al Ghiffari; Hidayatullah, Taufik; Cahyono, Yohana; Indah, Zainatuts Tsaniyah (Welfare : Jurnal Pengabdian Masyarakat, 2023)
The Pujasera Fishing Pond Revitalization Program through Festival Activities (P-FEST) is a strategic step in combating the serious challenges faced by village-owned enterprises (BUMDes) in Sumberpakem Village. Lack of innovation and marketing strategies, limited managerial skills among BUMDes member farmers, and declining demand for fish products are the main focus. Collaborative KKN students, collaborating with BUMDes administrators, collect data through surveys and interviews. P-FEST events, including batik educational tourism, collage competitions, cooking competitions, and MSME bazaars, involve elementary and middle school students in an effort to preserve batik crafts and develop the creativity of the younger generation. The service activity method uses the Asset-Based Community Development (ABCD) approach. The results include increased community participation and understanding, revitalization of the food court pool, as well as social and economic strengthening of Sumberpakem Village. This program aims to revive BUMDes businesses, revive the village economy, and introduce superior village products through collaborative activities involving the entire community. The P-FEST program and ABCD method encourage community independence in managing local resources to improve village welfare.